Chromatographic Methods for the Determination of Primula Acid 1 Content in Primulae extractum fluidum - Dedić, Mirza; Imamović, Belma; Bečić, Ervina; Gičević, Armina; Žiga-Smajić, Nermina; Medanhodžić-Vuk, Saira; Šober, Miroslav (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2020)
Primula veris L. (Primulaceae)is healing plant, whose root is officially used to treat cough associated with cold. Other reported indications are respiratory, thoracic and mediastinal disorders. These effects are result of high contents of triterpenoid saponins and phenolic glycosides. Primula acid 1 (PA 1, also primulasaponin 1) is main active component in Primula elatior L. This paper presents an optimized high pressure liquid chromatography (HPLC) method for the determination of primula acid 1 content in Primulae extractum fluidum. TLC was performed to check for the presence of the substance of interest. The determination was performed by reversed phase chromatography using C18 as a stationary phase. The mobile phase used for separation consisted of 0.2% H3PO4 and acetonitrile. This method was validated through different parameters. The detection limit for primula acid 1 was LD=10.41 µg/ml, and the quantification limitwas LQ=34.69 µg/ml. In order to determine the content of primula acid 1, a calibration curve was constructed, and the content of primula acid 1 was calculated by the equation of the calibration curve and was 0.2793 mg per gram of extract. The results and simple preparation of sample show that HPLC is the method of choice for this type of analysis.